If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 + -8(x + 1) = 2x + 7 Reorder the terms: 3x + 9 + -8(1 + x) = 2x + 7 3x + 9 + (1 * -8 + x * -8) = 2x + 7 3x + 9 + (-8 + -8x) = 2x + 7 Reorder the terms: 9 + -8 + 3x + -8x = 2x + 7 Combine like terms: 9 + -8 = 1 1 + 3x + -8x = 2x + 7 Combine like terms: 3x + -8x = -5x 1 + -5x = 2x + 7 Reorder the terms: 1 + -5x = 7 + 2x Solving 1 + -5x = 7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + -5x + -2x = 7 + 2x + -2x Combine like terms: -5x + -2x = -7x 1 + -7x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + -7x = 7 + 0 1 + -7x = 7 Add '-1' to each side of the equation. 1 + -1 + -7x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -7x = 7 + -1 -7x = 7 + -1 Combine like terms: 7 + -1 = 6 -7x = 6 Divide each side by '-7'. x = -0.8571428571 Simplifying x = -0.8571428571
| 4(56-34)= | | a-8=-4 | | -7w=-42 | | t/-2=-2 | | 6m=12 | | -7m^2-5m^2+4m^2= | | 3/2w+4=19 | | 3/2w+4=28 | | 7x+(6x-1)=90 | | n+4=15 | | d+5=0 | | b+6=7 | | Z/-6=-2 | | -19=t-8 | | 3+n=13 | | 4t=0 | | a+9=5 | | 7d=-14 | | 4=t+4 | | 14=a+8 | | a/3=-7 | | 19=k+7 | | t-1=0 | | x(5-x)+2= | | w-2=-11 | | -6a=-12 | | w+6=-6 | | 5+n=5 | | w+9=15 | | t/7=-6 | | k/4=-2 | | 6=n+2 |